Pengaruh Sikap dan Kepribadian Guru Terhadap Kepuasan Siswa dalam Layanan Bimbingan dan Konseling Kelas XI–IIS-1 SMA Negeri 1 Gido - Lase, Ukiran; Munthe, Mondang; Era, Justin Foera (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study aims to determine the influence of BK teachers' personality attitudes on student satisfaction in Guidance and Counseling services held at SMA Negeri 1 GIdo. The research approach is a quantitative approach with an associative type. The sample of this study was class XI.IIS-1 students who had attended guidance and counseling at SMA Negeri 1 Gido totaling 35 students. The data collection tool used in this study was an instrument in the form of a questionnaire. Based on the results of the study, it can be concluded that the attitude and personality of BK teachers jointly affect student satisfaction in Guidance and Counseling Services. The results of the hypothesis test, known R-Square value 0.474. This means that the attitude and personality of BK teachers affect student satisfaction in guidance and counseling services by 47.4%. This shows that simultaneously the attitude and personality of BK teachers have a significant effect on student satisfaction in guidance and counseling services. So that the more capable the attitude and the more personality of the BK teacher towards students, the higher the satisfaction of students in the Guidance and Counseling Service. The attitude of BK teachers has a positive effect so that the more capable the attitude of BK teachers will increase student satisfaction in Guidance and Counseling Services. The personality of the BK teacher has a positive effect so that the more capable the personality of the BK teacher will increase student satisfaction in the Guidance and Counseling Service